Disseminated tuberculosis presenting as chronic pancreatitis, a rare case report - Thakkar, Nihar R.; Beedkar, Anant N.; Gowda, Varun R.; Patil, Supriya S. (International Journal of Research in Medical Sciences, 2023)
Disseminated tuberculosis (TB) refers to concurrent involvement of at least two non-contiguous organ sites of the body, or involvement of the blood or bone marrow by tuberculosis process. Pancreatic TB is a rare manifestation of such a common disease possibly due to protective pancreatic enzymes. We described a case report of a patient who presented with chronic pancreatitis with pancreatic pseudocyst with empyema of left lung which intraoperatively was a psoas abscess which was managed by drainage of the abscess and Intercostal tube placement and thoracoscopic drainage of empyema and its adhesiolysis. Histopathology revealed tuberculous granulation tissue of psoas muscle biopsy and in thoracoscopic scrapings. Patient became symptomless since the surgery and initiation of anti-tubercular therapy.